Potential Study of Biopolymer-based Carboxymethylcellulose Electrolytes System for Solid-State Battery Application - M. I. N., Isa; Ahmad Salihin, Samsudin (Taylor & Francis, 2016)
This paper focused on study of potential biopolymer arboxymethylcellulose (CMC) as electrolyte system for application in solid-state battery, which was prepared via solution casting technique. The highest conducting CMC biopolymer electrolytes (BE) was achieved at 1.12 × 10−4 Scm−1 with addition of 25 wt% NH4Br and was improved to 3.31 × 10−3 Scm−1 when plasticized with 8 wt% EC. The solid-state battery was assembled using both systems with the configuration Zn +ZnSO4.7H2O // highest conducting BE // MnO2 and showed promising performance at room temperature. This work implies that the possible practical application of the present biopolymer CMC as a new invention of electrolytes system in the fabrication of electrochemical devices.